Exosomes in Ocular Health: Recent Insights into Pathology, Diagnostic Applications and Therapeutic Functions - Noelia Blanco-Agudín; Suhui Ye; Sara González-Fernández; Ignacio Alcalde; Jesús Merayo-Lloves; Luis M. Quirós (Biomedicines)
Exosomes are extracellular vesicles ranging from 30 to 150 nm in diameter that contain proteins, nucleic acids and other molecules. Produced by virtually all cell types, they travel throughout the body until they reach their target, where they can trigger a wide variety of effects by transferring the molecular cargo to recipient cells. In the context of ocular physiology, exosomes play a very important role in embryological development, the regulation of homeostasis and the immune system, which is crucial for normal vision. Consequently, in pathological situations, exosomes also undergo modifications in terms of quantity, composition and content, depending on the etiology of the disease. However, the mechanisms by which exosomes contribute to ocular pathology has not yet been studied in depth, and many questions remain unanswered. This review aims to summarize the most recent knowledge on the function of exosomes in the ocular system in healthy individuals and the role they play during pathological processes of a degenerative, infectious, neurodegenerative, vascular and inflammatory nature, such as keratoconus, keratitis, glaucoma, diabetic retinopathy and uveitis. Furthermore, given their unique characteristics, their potential as diagnostic biomarkers or therapeutic agents and their application in clinical ophthalmology are also explored, along with the main limitations that researchers face today in the field.